PAS mathematical models to achieve alignment - Monique Arkesteijn (A+BE: Architecture and the Built Environment)
The focus in this chapter is on the component mathematical models of PAS (see Figure 7.1 and Figure 7.2). PAS can only be performed if the system engineers are able to build a mathematical model of the problem situation for each of the pilot studies. In this chapter, I will show that the system engineers were able to do this for all three pilots.